The Impact of Combined Music and Tai Chi on Depressive Symptoms Among Community-Dwelling Older Persons: A Cluster Randomized Controlled Trial - Liao, S.J.; Tan, Maw Pin; Chong, Mei Chan; Chua, Yan Piaw (Taylor & Francis, 2018)
Background: The effectiveness of pharmacological treatment may be limited in older persons. Several studies using Tai Chi or music therapy separately confirmed positive effects in the reduction of depressive symptoms. We conducted a cluster randomized controlled trial to evaluate the possible synergistic effect of combined music and Tai Chi on depressive symptoms. Methods: One hundred and seven older adults with mild to moderate depressive symptoms were recruited from Ya'an city. Fifty-five participants were cluster randomized to combined music and Tai Chi group for three months, while the other fifty-two individuals were randomized to the control group that entailed routine health education delivered monthly by community nurses. The primary outcome of depressive symptoms was measured with the Geriatric Depression Scale (GDS) at baseline and monthly for three months. Results: At three-month follow-up, a statistically significant improvement in depressive symptoms was found in the intervention group compared with control group (F(3,315) = 69.661, P < 0.001). Following adjustments for socio-demographic data, the true effect of intervention on depressive symptoms was significant (F = 41.725, P < 0.01, η p 2 = 0.574). Conclusions: Combined music and Tai Chi reduced depressive symptoms among community-dwelling older persons. This represents an economically viable solution to the management of depression in highly populous developing nations.